Effects of Nursing Care using Neuman's Theory on the amount of Analgesic Drug, Sedative Drug, and Drug Withdrawal Syndromes in Critically Ill Pediatric Patients on Mechanical Ventilation at Songklanagarind Hospital - Yokrat, Paweena; Kaewvichit, Namtip; Kampan, Pilailak; Prasertsan, Pharsai; Thaworncheep, Supatcha (Princess of Naradhiwas University Journal, 2026)
Background and Objectives The Pediatric Intensive Care Unit at Songklanagarind Hospital has critically ill pediatric patients on ventilators who receive continuous pain and sedative medications for extended periods, increasing the high risk of withdrawal. Finding ways to reduce the amount of pain and sedative medications will help mitigate the severity and incidence of withdrawal. This research aimed to compare the amounts of pain and sedative medications and to compare the occurrence of withdrawal symptoms between critically ill pediatric patients on ventilators who receive nursing care based on Neuman's theory and those who receive standard nursing care. Methods This study was a quasi-experimental study conducted on 64 critically ill pediatric patients aged 1 month to 15 years receiving mechanical ventilation and opioid and benzodiazepine medications. The patients were divided into two groups: a control group of 32 patients and an experimental group of 32 patients. Data was collected group by group, starting with the control group. Research tools included 1) data collection tools, such as pediatric patient personal data records, analgesic and sedative drug dosage records, and the Withdrawal Assessment Tools (WAT-I) for assessing withdrawal symptoms; and 2) the experimental intervention, which was a nursing program based on Neuman's theory, including sleep promotion, touch, and speaking with critically ill pediatric patients by parents or carers. Data were analyzed using descriptive statistics, chi-square, Wilcoxon, and Fisher's exact test. Results There was no significant difference in the amount of analgesic and sedative drug and withdrawal symptoms between the experimental group receiving nursing care based on Neuman's theory and the control group receiving standard nursing care (p>.05). However, when comparing the total amount of medication received, the experimental group was able to reduce the use of the analgesic drug, as the fentanyl painkiller better than the control group (p<.05). Conclusion and Recommendation The nursing intervention based on Newman's theory was not able to reduce the average amount of analgesic and sedative drugs, including drug withdrawal symptoms. However, when comparing the total amount of medication received, it was found that the use of the analgesic drug Fentanyl could be reduced, and the average score for withdrawal symptoms was low. Nevertheless, a program based on Newman's theoretical concepts should be developed for nursing care for this pediatric patient group to improve its effectiveness.